FUSINITE OF FOSSIL COALS AS AN INFORMATION SOURCE ABOUT THE ANATOMY OF ANCIENT PLANTS - Kizil'stein L.Ya. (My University, 2006)
"Clarification" and ion and high-frequency etching of fusinite are described. These methods allow microscopic examination of fusinitized plant tissues in fine anatomical detail, revealing the outlines of cells, the structure of cell walls, the outlines of bordered pits, and, occasionally, even cellular microstructures. It is supposed that the effects of "clarification" and etching are caused by those optical differences between the composition of organic biopolymers that constituted the anatomical structures of plants that have been preserved in the fossil state. © Pleiades Publishing, Inc. 2006.
Keywords: ETCHING; FOSSIL PLANT ANATOMY; FUSINITE